ABERRANT PATTERNS DETECTION METHODS - Núñez Núñez, Rosa Mª; López Pina, José Antonio (Anales de Psicología / Annals of Psychology, 2006)
Aberrant patterns detection has a great usefulness in order to make tests and item banks with psychometric characteristics and validity analysis of tests and items. The most relevant and newest person-fit methods have been reviewed. All of them have been made in each one of main areas of Psychometry: Guttman’s scalogram, Classical Test Theory (CTT), Generalizability Theory (GT), Item Response Theory (IRT), Non-parametric Response Models (NPRM), Order-Restricted Latent Class Models (OR-LCM) and Covariance Structure Analysis (CSA).